PENANGGULANGAN KEMISKINAN DI SEKTOR PERTANIAN: KASUS PADA PROGRAM BEKERJA - Endro Gunawan; Bambang Irawan (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
In order to reduce poverty in the agricultural sector, the Ministry of Agriculture implements the BEKERJA program, which is an effort to empower poor farmers in farming multi-commodities, including laying hens, vegetables, fruit and plantation crops. The objective of this study is to understand the role of the program on increasing farmers' income and reducing poverty. This research was conducted in 11 provinces covering 38 districts which were the location of the BEKERJA program in 2018 and 2019. The data used were primary data collected through in-depth interviews of farmers participating in the program. The results of quantitative and qualitative descriptive analysis concluded that the program was quite successful in enhancing agricultural business activities among poor farmers, but it had not been able to increase farmers' income significantly. The number of poor farmers participating in the program only decreased by 1.48%. There are many challenges faced in empowering poor farmers, and therefore a strong commitment is needed to reduce poverty in the agricultural sector. To increase the effectiveness of these poverty reduction efforts, the empowerment of poor farmers in the future should be carried out as the following: (1) commodities developed are focused on the laying hens and vegetables farming, (2) farmers empowerment and provision of agricultural facilities should be continued at least until the farming activities is financially profitable, (3) technical guidance for cultivation should be strengthen, (4) beneficiaries of the program should be prioritized to young farmers, and (5) development a special program that is focussed for the poor farmers.